Leveraging Generative Artificial Intelligence for Digital Content Development to Promote Local Wisdom: A Community Empowerment Program in Mekarmaju Tourism Village, Bandung Indonesia - Ariyanti, Maya; M Yudha Febrianta; Mesayu Ana Hanifah Yahsallah; M Farhan Ramadhan (Edumedia Solution, 2026)
The rapid development of generative artificial intelligence (AI) presents an opportunity to accelerate digital content creation in community-based tourism destinations. This community service program aims to empower residents of Mekarmaju Tourism Village, Ciwidey, Bandung Regency, by increasing their capacity to develop digital content that promotes local wisdom through the use of generative AI tools. The program uses a participatory and community-centered approach, consisting of needs assessments, practical training, and mentoring activities involving village officials, youth organizations, state-owned enterprises (BUMN), and local micro, small, and medium enterprises (MSMEs). The training materials focus on AI-assisted content ideation, scriptwriting, visual design, short video script writing, and content planning for digital tourism promotion. The study results showed significant improvements in digital literacy, creative confidence, and participants' ability to produce digital content rooted in local culture. Participants successfully produced promotional content aligned with local narratives, including tourism visuals, social media captions, and content templates. The program demonstrated that generative AI can serve as an effective driver for community empowerment by reducing technical barriers to content production while maintaining the authenticity of local wisdom. This study contributes to the literature on community service and rural tourism development by highlighting the strategic role of AI in supporting sustainable digital transformation at the village level.